Seasonal response of nitrogen exchange fluxes to crab disturbance at sediment–water interface in coastal tidal wetlands - Guo-fen Hua; Shang-qing Liu; Xiang-dong Liu; Jin-li Li; Yue Fang; Wen-ting Xie; Xiang Xu (Water Science and Engineering, 2024)
Coastal wetlands are hotspots for nitrogen (N) cycling, and crab burrowing is known to transform N in intertidal marsh soils. However, the underlying mechanisms remain unclear. This study conducted field experiments and used indoor control test devices to investigate the seasonal response of nitrogen to crab disturbance at the sediment–water interface in coastal tidal flat wetlands. The results showed that crab disturbance exhibited significant seasonality with large seasonal differences in cave density and depth. Due to crab disturbance, nitrogen fluxes at the sediment–water interface were much greater in the box with crabs than in the box without crabs. In summer, NH4+-N showed a positive flux from the sediment to the overlying water, but NO2−-N and NO3−-N showed positive fluxes from the sediment to the overlying water only in early stages. In winter, NH4+-N showed a positive flux from the sediment to the overlying water, but NO2−-N and NO3−-N both exhibited positive and negative fluxes. These results indicated that the presence of crab burrows can cause the aerobic layer to move downward by approximately 8–15 cm in summer and directly promote nitrification at the sediment surface.